New issues of ILAM records - Tracey, Hugh (International Library of African Music, 1961)
The “AMA” 12" Long Playing records listed below have been recorded by the Library’s field recording unit since the last list published in Volume 11, No. 1 (1958). Each record contains approximately 36 to 40 minutes of recorded matter and is accompanied by sets of transcription sheets in quadruplicate containing classifications of language, types, instruments and notes on items.
Keywords: African Music